Effects of Synthesis Conditions on Rare Earth Doped Iron Oxide Catalyst for Selective Catalytic Reduction of NOx with NH3 - Ying Wei; Bingquan Wang; Ruiyi Ren; Rui Wang (Aerosol and Air Quality Research)
Abstract A series of rare earth-doped Fe-based oxide catalysts were prepared by co-precipitation method as Selective Catalytic Reduction (SCR) catalysts. The effects of the various rare earth species, doping amount of Sm, calcination temperature and the kind of precipitant on the deNOx activity of the catalysts were systematically investigated. The SO2 resistance performance was tested on the optimal catalyst. The catalysts have been characterized by X-ray diffraction (XRD), The X-ray photoelectron spectra (XPS), scanning electron microscopy (SEM) and Brunner Emmet Teller (BET). The results showed that the doping of Sm significantly improves the removal efficiency of Fe-based oxides. Sm0.075Fe0.925 catalyst showed the optimal deNOx performance and excellent resistance to SO2. At the optimal doping rate (0.075), the denitrification rate was close to 100% between 200 and 250°C. The calcination temperature has a significant effect on the catalyst. The order of catalytic activity for different calcination temperatures was 350°C ≈ 400°C > 450°C > 500°C. The Sm0.075Fe0.925 achieved 100% the de-NOx efficiencies at calcination temperatures of 350–400°C. It was also found that the deNOx performance of the catalyst prepared by using NH3·H2O as the precipitating agent was better than the catalyst prepared by using (NH3)2CO3 or NaOH as the precipitating agent. Normally a small amount of SO2 would render the catalyst inactive, but the Sm0.075Fe0.925 catalyst was basically regenerated after 0.05% SO2 removal in this resistance test.